ChemInform Abstract: 5‐Nitrosalicylic Acid as a Novel Matrix for In‐source Decay in Matrix‐Assisted Laser Desorption/Ionization Mass Spectrometry. Issue 16 (22nd April 2014) - Asakawa, Daiki
Abstract Review: 55 refs.